Ecological Systems Modelling of Information Behaviour: Theory to Increase Research Impact - Greyson, Devon L. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper reviews ecological models and approaches within LIS research, asserting that Information Behaviour researchers should activate our potential to impact public policy by applying Bronfenbrenner’s Ecological Systems Theory (EST). Two case studies of information behaviour studies re-modelled according to EST are presented as examples. Cette communication examine les modèles et les approches écologiques dans la recherche en BSI, argumentant que les chercheurs en comportement informationnel devraient activer notre potentiel à avoir un effet sur les politiques publiques, en appliquant la théorie des systèmes écologiques de Bronfenbrenner. Deux études de cas de comportements informationnels remodelés selon cette théorie sont présentées en exemple.